Journal Article Writing Assistance Program: An Effort to Improve Publication in Islamic University - Muhammad Farkhan; Awalia Rahma; Mauidlotun Nisa; Muhammad Azwar (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis mixed-methods study aimed to explore how the Faculty of Humanities carried out Journal Article Writing Assistance Program (JAWAP) in 2021, and determine its contribution to the participants’ English articles. MethodThis mixed methods research used a convergent mixed methods design that relied on 17 participants’ perception towards its implementation as the main data collected using questionnaire, interview, and document analysis. The quantitative data were analyzed using correlational statistics and compared with qualitative data to confirm or dis-confirm each other. FindingsThe study revealed that JAWAP worked in an online scheme where the communication between the participants and reviewers did not occur intensively. The study identified weaknesses in the review process, such as the article’s compliance with the author guidelines, lack of interdisciplinary discussion and collaboration with others, and the deservedness to be published in internationally journals. However, the study shows the JAWAP contributed significantly to the participants’ English articles. ConclusionJAWAP as an assistance program can help the participants to write quality English articles. To increase its contribution to the English article quality, the faculty should conduct the program intensively during the writing process openly in an intensive communication between reviewers and participants in small groups.